Early childhood caries and its associated factors among 5-years-old Myanmar children - Min, Saw Nay; Duangthip, Duangporn; Gao, Sherry Shiqian; Detsomboonrat, Palinee (Frontiers in Oral Health, 2024)
Introduction Children's oral health plays a crucial role in their overall well-being and there is a significant gap in our understanding of early childhood caries (ECC) in Myanmar. This study aims to bridge this knowledge deficit by investigating the prevalence, causes, and potential interventions for ECC in the Myanmar population, providing crucial insights for future dental health policies and practices. Methods Generally healthy 5-year-old kindergarten children from 7 districts in city were recruited. ECC was assessed through clinical examinations using decayed, missed, filled teeth (dmft). Additionally, demographic data of the children and their caregivers, along with information about the children's oral health-related behaviors, were gathered using a structured questionnaire. Results Out of the 496 children, the overall prevalence of dental caries was 87.1% (mean dmft score: 5.57, SD: 4.6). Caries experience was categorized as severe (45.8%) and non-severe (41.3%). Decayed teeth constituted the major component of the dmft index (97.8%). Multiple logistic regression analysis revealed two significant factors associated with ECC prevalence: late toothbrushing initiation (OR: 2.54, p = 0.001) and dental visit experience (OR: 2.46, p = 0.010). Discussion The study highlights the alarming ECC prevalence in 5-year-old children in Mandalay, Myanmar, with mostly untreated decayed teeth. The findings emphasize early preventive oral health measures for young children to reduce ECC burden in Myanmar.